A guru is born a novel - Bīto, Takeshi 1947- (Vertical, 2012)
"Kazuo, a haplessand aimless young man, happens upon a demonstration of an old guru's mystical powers and feels--for the first time in his life--a sense of purpose. He impulsively joins the guru's sect and is swept up into life in a religious order. The guru's right-hand man Shiva and Youth Group director Komamura have completely opposite views on faith and what the purpose of their order should be, and Kazuo has his eyes opened to the fact that behind the order's pious façade lies towering egos, financial trickery, betrayal, backstabbing and seduction."--P. [4] of cover
Keywords: Gurus / Fiction; Sects / Fiction; Mental suggestion / Fiction